APPLICATION OF VAT TO FINANCIAL SERVICES - Sharyar Kuanishbaevich Bisenbaev (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This study examines the application of VAT to the financial sectors and the implications of exempting financial services from VAT. An analysis of VAT collection from financial services and the consequences of VAT exemption from theoretical and practical points of view was conducted. The application of VAT to financial institutions is a very complex issue in the area of public finance. For various technical and practical reasons, financial services are generally exempt from VAT in most countries. The banking sector provides credit services and paid services to consumers. VAT exemption for financial services creates some distortions for banks and the real economy. Based on the results of the study, a conclusion was made on the application of VAT to financial services